Cultural Cognition and Ideological Framing Influence Communication About Zoonotic Disease in the Era of COVID-19 - Beall, Justin M.; Casola, William R.; Peterson, M Nils.; Larson, Lincoln R.; Carr, Wylie A.; Seekamp, Erin; Stevenson, Kathryn T.; Jackson, S Brent (Frontiers in Communication, 2021)
The efficacy of science communication can be influenced by the cultural values and cognitions of target audiences, yet message framing rarely accounts for these cognitive factors. To explore the effects of message framing tailored to specific audiences, we investigated relationships between one form of cultural cognition - political ideology - and perceptions about the zoonotic origins of the COVID-19 pandemic using a nationally-representative Qualtrics XM panel (n=1554) during August 2020. First, we examined differences in attitudes towards science (in general) and COVID-19 (specifically) based on political ideology. We found that, compared to conservatives and moderates, liberals trusted science more, were less skeptical of science, perceived greater risk from COVID-19, were more likely to believe in a wildlife origin of COVID-19, and were more likely to support restrictions on wildlife trade. Second, we examined the influence of cultural framing on the perceived validity of science related to COVID-19. Respondents were randomly assigned to one of three treatment groups: (1) a technocratic framing that highlighted feats of human ingenuity to overcome zoonoses; (2) a regulatory framing that highlighted regulations and expansions of protected areas for wildlife as a means to prevent zoonoses, and (3) a control article about traffic lights with no cultural framing. After reading the initial framing article, all three groups read the same fictional, yet factually accurate, ‘Nature Science study’ generated by the authors. An OLS regression model revealed a significant interaction between the technocratic framing and political ideology. Relative to the control group, the technocratic framing slightly increased perceived validity of the Nature Science study for conservatives, significantly lowered perceived validity for liberals, and had no impact on moderates. We did not detect any significant interaction between framing and political ideology for the regulatory framing. Findings of this study highlight the need to account for cultural cognitions when communicating about COVID-19 and other zoonotic diseases. Communication strategies carefully designed to resonate with ideologically diverse audiences may ultimately lead to bipartisan support for actions required to promote “One Health” approaches that reduce the impacts of zoonoses on human and environmental health.